Need Analysis in Designing Tourism Instructional Materials Based on Local Objects in South Sulawesi - Saiful Saiful; Firman Firman; Maharida Maharida; Rina Asrini Bakri (STAI Hubbulwathan Duri, 2022)
Tourist destinations In South Sulawesi have great potential for the global economic system that will invite a lot of foreign tourist activities. The role of education at university is the main buffer to produce qualified human resources in launching the wheels of tourism in this country. In teaching this course, there are still very few references based on local cultural wisdom therefore one of the reasons why the researchers raise the topic of empowering tourism objects in South Sulawesi in order to be able to develop this teaching material for students as prospective tourism actors other than being prospective teachers. A great EFL Instructional material should suit the students’ needs. The students' and lecturers’ impression is a crucial part of designing instructional materials. This paper reports the needs analysis of the students and lecturers in order to get the information about the students' and lecturers’ impressions of the existing materials on Tourism subject at a private university in Makassar. This research investigated the students’ needs by applying the survey method. This survey method was used to determine whether the local object materials meet the students’ needs in learning the tourism subject from a different perspective. This research utilized interviews and a questionnaire that were distributed to students and lecturers. This research contributed to designing further Tourism Instructional Materials Based on Local Objects such as syllabi, lesson plans, and coursebooks for university students